Melangkah Bersama dalam Pelayanan: Kedudukan Badan Ke-esaan Gereja sebagai Alat Pembaruan Iman dan Tindakan (International Forum of Researchers and Lecturers, 2024)
The role of the church in renewing people's faith through inclusive services. In the modern context, the church not only functions as a traditional place of worship but also as a social community that is active in improving the spiritual and emotional life of citizens. Through programs such as religious teaching, social services, and cultural activities, the church can be an effective tool for building moral awareness and providing support to those in need. The church also plays a role in social advocacy, promoting peace, and teaching universal values ​​that can be used in various aspects of life. By stepping together in this service, the church can unite society and help them towards a more positive and harmonious path. Thus, this topic highlights the potential of the church as a progressive and dynamic institution in an increasingly complex global era.